Science Processing Skill and Critical Thinking: Reviewed Based on the Gender - Darmaji, Darmaji; Kurniawan, Dwi Agus; Astalini, Astalini; Setiya Rini, Endah Febri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Skills are an essential aspect that every individual should have. Students' critical thinking ability in Indonesia is still in the low category. Based on the fact that science learning carried out by teachers in schools tends to use the lecture method in learning. It causes students to lack critical thinking skills. This study aims to analyze the effect of science process skills on critical thinking skills. This type of research is descriptive quantitative research through experimental methods. The sampling technique used is total sampling, with a sample of 60 practitioners. The methods used to collect data are observation and tests. The instruments used in collecting data are observation sheets and essay tests. Data analysis techniques used are descriptive statistics and inferential statistics. Data analysis obtained that the students' science process skills were considered good, but female students were more dominant. Meanwhile, critical thinking skills are also classified as critical and dominant in female students in the very critical category. Based on the study results, it was concluded that there was an influence of science process skills on students' critical thinking skills. It is hoped that this research can contribute to schools in Indonesia.